Some Results on Super Quasi-Einstein Manifolds. (15th February 2012) - Hui, Shyamal Kumar; Lemence, Richard S.
Abstract : This paper deals with the study of super quasi-Einstein manifolds admitting W 2 -curvature tensor. The totally umbilical hypersurfaces of S ( Q E ) n are also studied. Among others, the existence of such a manifold is ensured by a nontrivial example.